Four new phenolics and antiparasitic secondary metabolites from Flacourtia rukam Zoll. & Mortizi. Issue 14 (15th July 2022) - Afifi, Naglaa I.; Moawad, Abeer S.; Zaki, Mohamed A.; Rateb, Mostafa E.; Rashed, Mohammed H.; Saleh, Ibrahim G.; Hetta, Mona H.; Mohammed, Rabab M.
Abstract: Phytochemical investigation of Flacourtia rukam Zoll. & Mortizi ( F. rukam ) leaves and bark led to the isolation and characterization of seventeen compounds of which four phenolics were not previously described; 2-[(benzoyloxy)methyl]-phenyl- O - β -xylosyl-(1→2)- β -glucopyranoside (1), 2-[(benzoyloxy)methyl]-4-hydroxyphenyl- O - β -xylosyl-(1→2)- β -D-glucopyranoside (2 ), 2-hydroxy-5-(2-hydroxyphenoxy)phenoxy- β -glucopyranoside (3 ) and biphenyl-1, 1′, 2, 2′-tetraol (5 ). Interestingly, the later compound is known as a synthetic but this is the first report for its isolation from nature. Chemical structures were established using extensive analysis of spectroscopic data (1 D and 2 D NMR and HRESIMS). Biphenyl-1, 1, 2, 2′-tetrol (5 ) exhibited a good activity against Trypanosoma brucei trypomastigotes with IC50 = 6.66 ug/mL. Compounds 2, 5, 9, 10, 11 and 12 showed a good in-vitro anti-inflammatory activity using proteinase inhibitory assay. On the contrary, all tested compounds were inactive as antileishmanial or antimalarial. Graphical Abstract: UF0001